Calculation of Temperature Action of Flat Steel Box Girder of Long-Span Bridges Using a Joint Model of ARMA Mean and GARCH Variance - Jun Yang; Dacheng Zhao; Bin Chen; Gaoxin Wang (Shock and Vibration)
Using the monitoring temperature field data from the flat steel box girder, the time histories of temperature data and temperature difference data are investigated using the extreme value analysis method. Because the calculation of standard values of temperature action needs massive temperature field data, the simulation of daily extreme values of temperature data and temperature difference data is carried out by virtual of Probability Statistical Method. The seasonal and nonstationary trend terms are described using the weighted sum of a series of basic elementary functions. The random fluctuation term is represented by a joint model of ARMA mean and GARCH variance. Moreover, the yearly extreme values of temperature data and temperature difference data are considered as statistical variables, and their standard values of temperature action with 50-year return period are calculated by means of the general extreme value (GEV) distributive function. The research results can supply references for temperature action of flat steel box girder.